Clinical, Neurophysiological and Histopatological correlations in Pure Neural Leprosy - Pitta, Izabela Jardim Rodrigues; Mietto, Bruno de Siqueira; Camilo, Aron dos Santos; Antunes, Sergio Luiz Gomes; Sarno, Euzenir Nunes; Jardim, Marcia Rodrigues (Brazilian Journal of Case Reports, 2021)
Although neuropathy remains one of the most problematic issues faced by leprosy patients, the evolving process of its findings continues a challenge particularly in pure neural leprosy (PNL). We evaluated neurological examination, nerve conduction studies and histhopathological data of patients with PNL and ulnar neuropathy. Patients with longer duration of symptoms had reduction in the motor conduction velocities and patients with fibrosis in the biopsy had axonal damage in the nerve conduction studies. This suggests that focal demyelination may be present in leprosy patients at the moment of the diagnosis and be related to the duration of the neuropathy.